GAYA ETNOFOTOGRAFI DON HASMAN - Rosdian, Mevi (Institut Seni Budaya Indonesia Bandung, 2018)
This study aims to review the activities of photography done by Don Hasman in Ethnophotography. The combination of Ethnography and Photography, raises a photographic activity that is different from other photography activities. Knowledge of two fields of ethnography and photography is highly demanded to perform ethnofotografi activities. Don Hasman is better known as a photographer, who has never been an anthropologist. How do Don Hasman's style be in ethnotography? it is interesting to be an ethnophotographic study